PENERAPAN METODE TALKIN DALAM MENINGKATKAN MOTIVASI BELAJAR AL-QUR'AN PADA ANAK DAN REMAJA DI LINGKUNGAN MASJID (STUDI KASUS DI TPQ MASJID ABU BAKAR, JL. SEMANGKA, PADANG SERAI, KECAMATAN KAMPUNG MELAYU, KOTA BENGKULU, PROVINSI BENGKULU) - Chandra, Pasmah; Retno Wulansari, Dwi; Zulaikah, Siti; Revano Danendra, Aldo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the application of the Talkin method in enhancing Qur'anic learning motivation among children and adolescents at the Taman Pendidikan Al-Qur'an (TPQ) of Abu Bakar Mosque, located at Jl. Semangka, Padang Serai, Kampung Melayu District, Bengkulu City, Bengkulu Province. The Talkin method — a classical Islamic pedagogical approach grounded in oral transmission (talaqqi musyafahah) — is analyzed through its motivational impact on learners aged 5–17. Using a descriptive-qualitative approach with data collected through participatory observation, in-depth interviews, documentation, and Focus Group Discussion (FGD), this study finds that the Talkin method significantly increases intrinsic and extrinsic motivation, as evidenced by improved attendance rates (from 68% to 91%), greater enthusiasm for recitation practice, and measurable progress in reading proficiency across all assessed dimensions. Motivational gains are attributed to four key mechanisms: direct emotional bonding between teacher and learner, immediate corrective feedback, the cultivation of a sense of spiritual progression, and consistent positive reinforcement. Challenges include a non-optimal teacher-to-student ratio and the need for parental involvement. The study recommends targeted recruitment of qualified instructors and integration of gamified progress-tracking systems to sustain long-term motivation.